Middle East Oil Show and Conference 1999
DOI: 10.2118/53227-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using 3D Integrated Modelling to Manage the Fractured Natih Field (Oman)

Abstract: This paper was prepared for presentation at the 1999 SPE Middle East Oil Show held in Bahrain, 20-23 February 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…4,5) confirmed that full GOGD with oil rim lowering was the most attractive way for the continued development of the Natih Field. It was, thereafter, implemented in the Natih-A, together with crestal gas injection and peripheral water production.…”
Section: Water and Gas Injection (1972-82) -mentioning
confidence: 79%
See 1 more Smart Citation
“…4,5) confirmed that full GOGD with oil rim lowering was the most attractive way for the continued development of the Natih Field. It was, thereafter, implemented in the Natih-A, together with crestal gas injection and peripheral water production.…”
Section: Water and Gas Injection (1972-82) -mentioning
confidence: 79%
“…The initial production behavior of the Natih filed (Figs. [3][4][5] showed well off-take up to 2000 m3/d and total field production building up to more than 15000 m3/d. Early developing water cut and fast movement of fluid contacts were totally in line with a fractured reservoir.…”
Section: Field Development Historymentioning
confidence: 97%
“…It is believed that gas injection may postpone upward migration of WOC through the fractures known as coning/fingering (Zaitoun et al, 1999). It is stated that among all oil recovery mechanisms, the highest recovery efficiency belongs to gas-oil gravity drainage (GOGD), however, the recovery rates during isothermal GOGD are reported to be considerably low (Eikmans and Hitchings, 1999). Therefore, for economical oil recovery through the GOGD mechanism, it requires to be assisted by other compatible mechanisms to defeat the low oil drainage rate Macaulay et al, 1995;Hamed et al, 2001;Ayatollahi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, the matrix of such reservoirs contains the oil, while the fractures provide the flow paths. In such reservoirs, oil production can be improved by making use of gas/oil gravity drainage [see O'Neill (1988), Novinpour et al (1994), Saidi (1996), and Eikmans and Hitchings (1999)]. …”
Section: Field Casementioning
confidence: 99%